2012
DOI: 10.1002/cvde.201106950
|View full text |Cite
|
Sign up to set email alerts
|

Zirconocene Alkoxides, Promising Precursors for MOCVD of Zirconium Dioxide Thin Films

Abstract: Some new volatile bis-cyclopentadienyl zirconium alkoxides of the type Cp2Zr(OR)(OtBu) (R = iPr, Et, Me) is synthesized by the reaction of the corresponding KOR with the intermediate Cp2ZrCl(OtBu). Moreover, an alternative and convenient synthesis of Cp2Zr(OtBu)2, based on the reaction of Cp2ZrCl2 with an excess of tert-butanol and triethylamine, is reported. The obtained compds. are identified by chem. analyses, thermogravimetric measurements, IR (IR), NMR (NMR) spectroscopy, and mass spectrometry (MS). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Recently, Sartori et al reported a nano‐indentation hardness of 6 to 10 GPa for ZrO 2 thick film (2 μm) on a stainless‐steel substrate prepared by MOCVD from a zirconium alkoxide precursor. It is not straightforward to make a direct comparison between the hardness values reported by Sartori et al with our values but, generally, we could take the hardness value in indentation depth of 1200 nm as reported by Sartori et al to compare with our hardness values on thin (400 nm) films of ZrO 2 ; in both cases, the hardness values were about 6 GPa.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Recently, Sartori et al reported a nano‐indentation hardness of 6 to 10 GPa for ZrO 2 thick film (2 μm) on a stainless‐steel substrate prepared by MOCVD from a zirconium alkoxide precursor. It is not straightforward to make a direct comparison between the hardness values reported by Sartori et al with our values but, generally, we could take the hardness value in indentation depth of 1200 nm as reported by Sartori et al to compare with our hardness values on thin (400 nm) films of ZrO 2 ; in both cases, the hardness values were about 6 GPa.…”
Section: Resultssupporting
confidence: 50%
“…For MOCVD, the film properties are strongly dependent on the precursors employed. Numerous references can be found in the literature on the use of chlorides, nitrates, alkoxides, diketonates, fluorinated diketonates, cyclopentadienyls, etc., however some of these precursors suffer from certain drawbacks. The alkyl amides of Zr are another class of compounds that are widely used for the ALD of ZrO 2 thin films, but less investigated for MOCVD applications since they are extremely sensitive to air and moisture, and have lower thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 h) and even then may be incomplete, 47 and for the synthesis of the tert -butoxy derivative Cp 2 TiCl(O t Bu) ( 3 ), we investigated halide metathesis instead. This approach has been used to form Cp 2 ZrCl(O t Bu) in THF, 23 although the solution route fails for Cp 2 HfCl(O t Bu). 26f Mechanochemical activation works successfully with both of the heavier group 4 metals and it was adopted for the preparation of 3 .…”
Section: Resultsmentioning
confidence: 99%
“…26f Similarly, the reaction of Cp 2 ZrCl 2 and (Li or Na)[O t Bu] yields an inseparable mixture of Cp 2 ZrCl(O t Bu) and Cp 2 Zr(O t Bu) 2 , even with the use of more than 2 equiv of the alkoxide. 23…”
Section: Introductionmentioning
confidence: 99%